Tandem Architectures for Artificial Thylakoid Membranes - Engelbert Redel (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2023)
In this concept paper, new layered materials, such as multilayer hybrid systems, are described. These materials can be implemented into novel biomimetic devices, which can act as artificial photosystems or as "artificial thylakoid membranes" e.g. for the splitting of water. The architecture can be based on active nanoparticles or small catalytic clusters which can be synthesized from robust, inexpensive, and abundant material precursors. These multi-layered architectures can act as "artificial thylakoid membranes", which can mimic the photosynthetic apparatus on the nanoscale. The development of "artificial thylakoid membranes" and tandem devices promises a strong impact and benefits for the field of artificial photosynthesis and the development of artificial leaves.